Publisher’s Note: A survey of Aquacultural activities in China - Oghale, Egbabor (Advances in Aquaculture and Fisheries Management, 2013)
China, with one-fifth of the world's population, accounts for two-thirds of the worlds reported aquaculture production. The People's Republic of China is vast. Its territory sprawls over 9.6 million km2. The distance from borders in the east to those in the west measures 5 000 km and from north to south it spans over 5 500 km. China's present population is about 800 million.